The Effect of LC 5E Learning Model Combined with Make a Match on the Cognitive Learning Outcomes of High School Students on Acid Base Materials - Hafiz Radyastuti; Endang Budiasih; Dedek Sukarianingsih (J-PEK (Jurnal Pembelajaran Kimia), 2020)
Chemistry materials required that students must memorize and understand all of the concepts. Acid base is one of chemistry materials which is considered difficult. One solution to overcome the difficulty in learning acid base materials is change the learning method from one way to two ways that more focus on student (student centered) with reference to the constructivist approach LC 5E and cooperative learning Make a Match. Therefore, this research was conducted with the aim to: (1) describe the feasibility of students who learned acid-base materials use the LC 5E-Make a Match learning model,(2)determine differences in students cognitive learning outcomes that learned using the LC 5E-Make a Match learning model and that learned to use the LC 5E learning model in acid-base materials. This research used a quasi-experimental design with design models of two groups. The two classes were given same acid-base materials with different learning model. The average of student cognitive learning outcomes that learned using the LC 5E-Make a Match learning model (=84,06) was higher than students that using the LC 5E (79,89).